Prawo wyborcze i system partyjny Bułgarii 1990-2009 - Maksymow, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The article presents the contemporary debate about political and suffrage transformation in Bulgaria. Bulgarian political and electoral system evolved between 1990-2009. It is worth noting that it is still characterized by minimal political and party stability. The swing of the electoral preferences is large, which results in changes in the running of the cabinet. It means that the political system is unconsolidated. By contrast, the Bulgarian electoral system is multimandate and underwent a number of reforms. A great deal of attention in legislation is given to the financial support for election campaigns and to complement it with the d' Hondt method.
SUFFRAGE AND THE POLITICAL PARTY SYSTEM IN BULGARIA BETWEEN THE YEARS 1990-2009
Keywords: political and suffrage transformation; changes of running the cabinet; unconsolidated; d' Hondt method